PENGARUH RETURN ON INVESTMENT (ROI), EARNING PER SHARE (EPS) DAN DIVIDEN PER SHARE (DPS) TERHADAP HARGA SAHAM - Setiawan, Ade Budi; Anwar , Saepul; Sriwahyuni, Irma (Universitas Djuanda, 2021)
Stock Price is the price that occurs on the stock exchange at a certain time which is determined by market players and is formed from the supply and demand in the capital market. This research was conducted to determine how much influence Return On Investment, Earning Per Share and Dividend Per Share on share prices simultaneously and partially in consumer goods industrial sector companies listed on the Sharia Securities List 2015-2019. Sampling using purposive sampling method so that a total sample of 9 companies was obtained. This study uses multiple linear regression data analysis techniques. The results of this study indicate that simultaneously ROI, EPS and DPS have an effect on stock prices. Partially only ROI and EPS have a significant positive effect on stock prices, while DPS does not have a significant effect on stock prices.